IMPROVING THE LOVE OF READING OF CHILDREN IN REMOTE AREA THROUGH CHILDREN’S BOOKS - Herawati, Herawati; Neprializa, Neprializa (LPPM STKIP PGRI Bandar Lampung, 2019)
Reading plays an important role to help people develop their knowledge and broaden their horizon. This research focuses on the children reading motivation in remote area. Two hundred and six children are involved in this study. They are grouped into experiment and control group. The experiment group was given children’s books in order to improve their reading motivation. To know the improvement, this study used questionnaire by Wigfield and Guthrie to be analized through SPSS 20. The result shows that children in the experiment group are more motivated than the control one. Based on the Mean result, there is significant improvement between pre and post test in experiment group; 67.53 to 81.42. In the same line, the result of Tcount 26,747 > t tabel 1,986, it means there is significant difference between pre and post result. Meanwhile, The mean of Control group is not significant improvement; 68.08 to 68.05. Control group also has Tcount 1,731 < Ttabel 1,986 that means there is no significant difference between pre and post result. It can be concluded that children’s books are useful to improve the children’s reading motivation or the love of reading in remote area.